INFLUENCE OF DIFFERENT TYPES OF RETRACTION THREADS ON THE DEGREE OF GINGI RECESSION - Egamov Sheroz Anvarovich, Burxonova Zarafruz Qobilovna (Journals Park Publishing, 2023)
Gingival retraction is a critical procedure necessary to obtain a more accurate impression in the manufacture of indirect restorations. The correct expansion of the periodontal sulcus remains one of the most critical procedures. In this regard, it is necessary to choose such retraction threads and retraction techniques that would minimize tissue trauma and would eliminate irreversible loss of soft tissues in height. Gingival retraction was first described in 1941 by Thompson. Now the dental market presents a large number of materials for this procedure, the leading place among which is occupied by retraction threads.